2019
DOI: 10.5812/numonthly.88677
|View full text |Cite
|
Sign up to set email alerts
|

Holmium: YAG Laser Incision of Bladder Neck Contracture Following Radical Retropubic Prostatectomy

Abstract: Background: No consensus management is available for the bladder neck contracture (BNC) secondary to radical retropubic prostatectomy (RRP). We present our experience of a technique in which holmium: YAG surgical laser was utilized transurethrally to incise the stenotic area. Methods: Incisions with holmium: YAG surgical laser were made in 34 subjects with BNC between January 2012 and May 2018. Medical charts were reviewed to evaluate related data including medical history, international prostate symptoms scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Today, the laser has an excellent application in urologic diseases. [22][23][24] Endoscopic laser lithotripsy (LL) is frequently used to manage patients with urolithiasis. 8,25 A number of lasers have been used for LL, of which the Ho:YAG has become one of the most frequently used one.…”
Section: Discussionmentioning
confidence: 99%
“…Today, the laser has an excellent application in urologic diseases. [22][23][24] Endoscopic laser lithotripsy (LL) is frequently used to manage patients with urolithiasis. 8,25 A number of lasers have been used for LL, of which the Ho:YAG has become one of the most frequently used one.…”
Section: Discussionmentioning
confidence: 99%
“…13 RP should be recommended in patients with a long life expectancy, poorly differentiated tumors or high PSA levels after TURP. 33,34 RP provides ten-year biochemicalfree survival rates as high as 79-98% and 74-88% in T1a and T1b cases, respectively. 12,35,36,37 Matanhelia et al showed that curative treatments need to be considered for younger cases with a long life expectancy or patients with higher-risk disease.…”
Section: Treatmentsmentioning
confidence: 99%
“…9 The Holmium laser has a good penetration depth, which helps in staunching blood; it is also used for other urologic surgeries, including urolithiasis, 10,11 bladder tumor, 6 genital skin lesion, 12 and urethrotomy. 13,14 The Holmium laser enucleation of the prostate (HoLEP) was introduced about 20 years ago as a surgical treatment for the lower urinary tract symptom (LUTS) resulting from BPH. 15 Despite some drawbacks such as a special equipment requirement and a steep learning curve, it seems that HoLEP is an efficient surgical approach to BPH.…”
Section: Introductionmentioning
confidence: 99%